2013
DOI: 10.2500/aap.2013.34.3654
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of anaphylaxis in children referred to a tertiary care center

Abstract: Anaphylaxis is a potentially life-threatening condition. There are limited data about the etiology and the clinical characteristics in developing countries. This study aimed to investigate the clinical characteristics of anaphylaxis patients attending our pediatric allergy clinic. We conducted a prospective analysis of patients who were admitted to our allergy clinic for anaphylaxis from 2010 to 2012. Ninety-six patients were evaluated during the study period. The mean age was 7.4 ± 5.2 years. Venom, food, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 0 publications
3
28
2
8
Order By: Relevance
“…38 The association of a biphasic reaction with the severity of the initial reaction has just recently emerged as a potential risk factor. 39 23,34 Although these studies provide some insight about this association, the reported cases are too small to reliably predict this association. Also, the definition of severity used in these studies is inconsistent and not based on objective scoring.…”
Section: Previous Studiesmentioning
confidence: 82%
“…38 The association of a biphasic reaction with the severity of the initial reaction has just recently emerged as a potential risk factor. 39 23,34 Although these studies provide some insight about this association, the reported cases are too small to reliably predict this association. Also, the definition of severity used in these studies is inconsistent and not based on objective scoring.…”
Section: Previous Studiesmentioning
confidence: 82%
“…9,10 PBA occurs infrequently in adults with anaphylaxis, with a prevalence ranging from 0 to 20%. [6][7][8]11,12 Few studies have evaluated the association between glucocorticoid use and anaphylaxis in adults. In one Canadian ED, 55% of patients with uniphasic anaphylaxis and 35% of those with biphasic anaphylaxis received glucocorticoids, a difference that did not achieve statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…In another Turkish study on pediatric anaphylaxis in children, which included 96 patients seen at a pediatric allergy clinic in a tertiary care center, 27% of the cases were attributed to drugs and, in another report on 34 cases of severe anaphylaxis in children seen in a pediatric allergy department, 61.8% of the cases analyzed were caused by drugs …”
Section: Epidemiologymentioning
confidence: 99%